Study of Development Planning and Spatial Policy of Mapanget Sub-district, Manado as a New City Center: A Review - Manakane, Susan E; Latue, Philia Christi; Rakuasa, Heinrich (Nusantara Journal of Behavioral and Social Science, 2023)
The policy in dividing the KBI and KTI regions is intended to avoid development imbalances that occur in Indonesia. Development in Eastern Indonesia is considered disproportionate and only focused on the Western Region. But now the priority of regional development will be focused on Eastern Indonesia. As a large city in North Sulawesi that is included in Eastern Indonesia, Manado has a strategic location as an investment gateway to economic growth in Eastern Indonesia, this is the background for the development plan of Mapanget sub-district which is included in the Manado City area to become a new city center. This research aims to assess the feasibility of the Mapanget area as the object of this strategic project. The method used was a literature study in combination with the availability of secondary data obtained from research, records and provisions related to the analysis of new city development. Based on the results of the various elements of new city development such as residential areas, health and education facilities, trade, services and industry, and population accessibility have experienced large growth in the period (2007-2019) or in the last twelve years. In terms of development planning, there are also complete guidelines that are based on an in-depth study of various aspects, so it can be concluded that Mapanget Sub-district is strategic enough for the development of a New City in Eastern Indonesia. Abstrak: Kebijakan dalam pembagian wilayah KBI dan KTI dimaksudkan untuk menghindari ketimpangan pembangunan yang terjadi di Indonesia. Pembangunan di Kawasan Timur Indonesia dirasa kurang proporsional dan hanya terfokus di Kawasan Barat saja. Namun saat ini prioritas pengembangan wilayah akan difokuskan ke Timur Indonesia. Sebagai Kota besar di Sulawesi Utara yang temasuk Kawasan Timur Indonesia, Manado memiliki lokasi yang strategis sebagai gerbang investasi terhadap pertumbuhan ekonomi di Timur Indonesia, Hal ini melatarbelakangi rencana pembangunan kecamatan Mapanget yang termasuk wilayah Kota Manado menjadi pusat Kota baru. Dilakukan penelitian yang bertujuan mengkaji kelayakan wilayah Mapanget sebagai objek dari proyek strategis ini. Metode yang dilakukan dengan studi literatur dan kombinasi dengan ketersediaan data sekunder yang diperoleh dari penelitian, pencatatan dan ketetapan yang berhubungan dengan analisa pembangunan kota baru. Berdasarkan hasil dari berbagai unsur pembangunan kota baru seperti wilayah hunian, sarana kesehatan dan pendidikan, perdagangan, bidang jasa dan industri, serta aksesibilitas penduduk telah mengalami pertumbuhan yang besar dalam periode (2007-2019) atau dalam dua belas tahun terakhir. Dari segi perencanaan pembangunan juga tersedia kelengkapan pedoman yang berdasarkan kajian mendalam terhadap beragam aspek, maka dapat disimpulkan bahwa Kecamatan Mapanget cukup strategis untuk pembangunan Kota Baru di Kawasan Timur Indonesia.